A Novel Wideband Bandpass Filter using H-shaped DGS - Van-Phuong Do; Duy-Manh Luong; Chi-Hieu Ta; Minh-Tan Doan (Institute of Advanced Engineering and Science, 2018)
This paper presents a novel compact wide-band bandpass filter (BPF) having good selectivity. It is designed using a dual-plane structure which consists of a parallel-coupled microstrip line on the upper surface and three H-shape defected ground structures (DGS) on the ground plane. By adding three H-shape DGS units on the ground plane, then properly adjusting their dimensions and position, the bandwidth and selectivity of the designed filter can be significantly improved. A compact prototype of wide-band microstrip bandpass filter has been designed, fabricated and measured for the wireless systems applications. The filter exhibits a center frequency at 4.8 GHz, passband from 2.8 GHz to 6.8 GHz with best insertion loss and return loss of 0.8 dB and 40 dB, respectively. The measured results agrees well with the theoretical expectations validating the proposed design.